PENGAWASAN PEMERINTAH KOTA PEKANBARU TERHADAP PELARANGAN PEMASANGAN REKLAME ROKOK DI KAWASAN TANPA ROKOK (KTR) TAHUN 2019 – 2020 - Tryandani, Nefy; Harirah, Zulfa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
No-smoking areas are a way to reduce health-harming tobacco smoke pollution, tobacco smoke can cause lung cancer, heart disease, asthma in children, and sudden infant death. Non-smoking areas include health service facilities, teaching and learning places and other places as regulated in Pekanbaru Mayor Regulation No. 39/2014 on No Smoking Areas. One of the prohibitions is the installation of cigarette billboards in the No-Smoking Area of Pekanbaru City. However, the supervision is still weak since the Mayor Regulation was implemented until 2019-2020. The local government is still cheating on cigarette billboards in the no-smoking area. Lack of firm sanctions, and a lack of compliance by employers with the Perwako. The formulation of the problem of this research is: